2010
DOI: 10.1200/jco.2008.21.6994
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Pazopanib in Patients With Metastatic Renal Cell Carcinoma

Abstract: Pazopanib demonstrated durable activity in patients with advanced RCC and was generally well tolerated in this population. These findings support the further development of pazopanib in advanced RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
181
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(192 citation statements)
references
References 13 publications
9
181
0
2
Order By: Relevance
“…Clinical data were obtained from a multicenter, open‐label phase II study (NCT00244764) 16. We had access to a subset of 47 patients, aged 43 to 79 years, with advanced and/or metastatic RCC of predominantly clear‐cell histology and obviousness of measurable disease by Response Evaluation Criteria in Solid Tumors (RECIST).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical data were obtained from a multicenter, open‐label phase II study (NCT00244764) 16. We had access to a subset of 47 patients, aged 43 to 79 years, with advanced and/or metastatic RCC of predominantly clear‐cell histology and obviousness of measurable disease by Response Evaluation Criteria in Solid Tumors (RECIST).…”
Section: Methodsmentioning
confidence: 99%
“…The phase II RCC study (VEG102616, Study 1) had 225 participants (Hutson et al, 2010) and the phase III RCC study (VEG105192, Study 2) had 435 participants (Sternberg et al, 2010). All patients from Study 1 and 290 patients from Study 2 received pazopanib (800 mg daily); the remaining 145 patients in Study 2 were randomised to the placebo arm.…”
Section: Patientsmentioning
confidence: 99%
“…It is currently under clinical development for the treatment of multiple tumour types (Altorki et al, 2008;Friedlander et al, 2008;Sleijfer et al, 2009;Taylor et al, 2009;Sternberg et al, 2010). Clinical meaningful efficacy was observed in pazopanib-treated patients with RCC (Hutson et al, 2010;Sternberg et al, 2010). The safety profile of pazopanib was generally acceptable and tolerable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although pazopanib has been developed and is currently being clinically used as an anti-angiogenesis agent, 8,20 direct antitumor effects of pazopanib have been described in the published literature for several tumor cells, including, multiple myeloma, 10 HER2 þ breast cancer, 11 lung cancer, 12 and chronic lymphocytic leukemia cells. 13 The dose-effectiveness of pazopanib against synovial sarcoma cells in the present study was comparable to the results of these studies which showed an IC 50 value ranging between approximately 2 and 15 mg/ml.…”
Section: Discussionmentioning
confidence: 99%